DIETARY HABITS OF MODERN HIGH SCHOOL AND STUDENT GIRLS ACCORDING TO THE QUESTIONNAIRE DESIGN - O. YA. Leshchenko (Acta Biomedica Scientifica, 2012)
As a result of questioning of high school and student girls of Irkutsk region we got data on the adequacy and. condition of their nutrition. The nutrition of most of high, school and. student girls is unsatisfactory according to the indices of structural and. biological value of food.